2014
DOI: 10.1155/2014/315375
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Factor IX Produced from Transgenic Porcine Milk

Abstract: Production of biopharmaceuticals from transgenic animal milk is a cost-effective method for highly complex proteins that cannot be efficiently produced using conventional systems such as microorganisms or animal cells. Yields of recombinant human factor IX (rhFIX) produced from transgenic porcine milk under the control of the bovine α-lactalbumin promoter reached 0.25 mg/mL. The rhFIX protein was purified from transgenic porcine milk using a three-column purification scheme after a precipitation step to remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…FAM20C‐kinase is present in plasma and it is synthesized by liver implicated in biomineralization, including the small integrin‐binding ligand and liver‐secreted N‐linked glycoproteins like FIX or factor V . Recently, a new rFIX produced by porcine mammalian cells and secreted in porcine milk has been described with improved post‐translational modifications such as activation peptide phosphorylation at 40% . In accordance with this data, we may speculate that the casein‐kinase present in the milk might contribute to the phosphorylation of the molecule.…”
Section: Resultssupporting
confidence: 65%
“…FAM20C‐kinase is present in plasma and it is synthesized by liver implicated in biomineralization, including the small integrin‐binding ligand and liver‐secreted N‐linked glycoproteins like FIX or factor V . Recently, a new rFIX produced by porcine mammalian cells and secreted in porcine milk has been described with improved post‐translational modifications such as activation peptide phosphorylation at 40% . In accordance with this data, we may speculate that the casein‐kinase present in the milk might contribute to the phosphorylation of the molecule.…”
Section: Resultssupporting
confidence: 65%
“…The collected milk contained 1 g/L of this protein [48]. Other recombinant human proteins involved in the coagulation process, such as factor VIII [49], factor IX [50,51], von Willebrand factor [52], were also successfully obtained in the porcine mammary gland. Furthermore, the line of transgenic pigs producing functional recombinant human erythropoietin in their milk was demonstrated.…”
Section: Pigs As Bioreactors For Pharmaceutical Productsmentioning
confidence: 99%
“…The WAP protein is specifically expressed in the mammary gland and is controlled by hormones and developmental signals during pregnancy [37]. Many studies have confirmed that the mammary glands of transgenic animals can serve as bioreactors to produce valuable therapeutic proteins [38][39][40].…”
Section: Discussionmentioning
confidence: 99%